The Scarlet Car - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Scarlet Car" by Richard Harding Davis is a novel written during the late 19th century. The story revolves around a group of young adults, primarily focusing on Winthrop and Beatrice Forbes, as they embark on a tumultuous journey to a football game, intertwined with personal dynamics and societal norms of the time. As the characters navigate various obstacles, including mechanical failures and interpersonal conflicts, the backdrop of scholarly rivalries amplifies the significance of their relationships. At the start of the novel, the main characters are introduced as they prepare for the football game between Harvard and Yale. Winthrop, enamored with Beatrice, faces jealousy and frustration due to her engagement to Ernest Peabody. Complications arise when Peabody's insistence on Beatrice not joining the group for their excursion leads to a tense atmosphere. As they make their way along the route in the titular Scarlet Car, a series of mishaps, including breakdowns and the intrusion of unforeseen circumstances, create humor, tension, and an opportunity for character development. The stage is set for a blend of adventure and exploration of themes of love, friendship, and societal expectations in a rapidly modernizing world. (This is an automatically generated summary.)
Release date is 1995-11-01
Keywords: Humorous stories; Love stories; Automobiles -- Fiction; Automobile driving -- Fiction